Flavouring methods of gaharu tea: article / Muhammad Danial Arieff Mohd Ghafoor and Habsah Alwi - Mohd Ghafoor, Muhammad Danial Arieff; Alwi, Habsah (2019)
Tea is one of the most consumed beverages in the world. While gaharu tea holds many benefits, the bitter taste makes it hard for consumer to drink this tea. Therefore this research objective is to study the best methods to flavour gaharu tea, the best flavour to infuse with the gaharu tea and the effect of adding flavour to antioxidant properties of gaharu tea. There are three methods of flavouring gaharu tea which is inclusion method, artificial flavouring method and mixture of both method. Inclusion methods is where chunk of dried fruits is added into the tea leaves and mixed together evenly. Artificial flavouring is where artificial flavours were sprayed on top of the leaves and mixed evenly. Lemon, strawberry and mint flavour are used in this experiment. Based on the DPPH assay, the scavenging activities for original gaharu tea is 85.43%. Lemon artificial flavouring methods indicates the highest scavenging activities which is 95.22%. Meanwhile, the pH of original gaharu tea is 6.30 which is neutral. Addition of lemon chunk makes the tea acidic which lowers the pH to 3.00. Flavour test was conducted among 20 participant to find out the best flavour. They were required to try all the tea with different flavour and different flavouring methods. The most favourable flavour is lemon flavour and the best method in flavouring gaharu tea is mixture of inclusion and artificial flavouring method.